2011
DOI: 10.1261/rna.2697111
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of Nro1/Ett1: a protein involved in translation termination in S. cerevisiae and in O2-mediated gene control in S. pombe

Abstract: In Saccharomyces cerevisiae, the putative 2-OG-Fe(II) dioxygenase Tpa1 and its partner Ett1 have been shown to impact mRNA decay and translation. Hence, inactivation of these factors was shown to influence stop codon read-though. In addition, Tpa1 represses, by an unknown mechanism, genes regulated by Hap1, a transcription factor involved in the response to levels of heme and O 2 . The Schizosaccharomyces pombe orthologs of Tpa1 and Ett1, Ofd1, and its partner Nro1, respectively, have been shown to regulate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…Having lost catalytic potential due to redundancy, the CTD may have retained or gained function(s) in substrate and/or binding partner recognition, stabilization, and/or oligomerization. A role for the non-catalytic CTD in the OGFOD1 subfamily in binding to the uS12 substrate, or other binding partners, seems likely; it is reported that the CTDs of both Ofd1 and Tpa1p interact with Nro1 and Ett1, respectively ( Lee et al., 2009; Rispal et al., 2011 ). Non-DSBH domains have been shown to be important in oligomerization and substrate binding selectivity in the case of other 2OG oxygenases, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having lost catalytic potential due to redundancy, the CTD may have retained or gained function(s) in substrate and/or binding partner recognition, stabilization, and/or oligomerization. A role for the non-catalytic CTD in the OGFOD1 subfamily in binding to the uS12 substrate, or other binding partners, seems likely; it is reported that the CTDs of both Ofd1 and Tpa1p interact with Nro1 and Ett1, respectively ( Lee et al., 2009; Rispal et al., 2011 ). Non-DSBH domains have been shown to be important in oligomerization and substrate binding selectivity in the case of other 2OG oxygenases, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although the biological roles for uS12 hydroxylation are still emerging, it has been reported that in yeast it can regulate translation in a sequence context dependent manner and that it is involved in stress responses ( Saito et al., 2010; Katz et al., 2014; Loenarz et al., 2014; Singleton et al., 2014 ). Ofd1, a homolog of OGFOD1/Tpa1p from Schizosaccharomyces pombe , binds to the helical repeat protein Nro1 in an O 2 -dependent manner ( Rispal et al., 2011; Yeh et al., 2011 ), thus inhibiting Ofd1 binding to Sre1N, a homolog of the sterol regulatory element binding protein ( Lee et al., 2009 ). In humans, a distinct ROX subfamily, more closely related to the JmjC domain subfamily, comprising MYC-induced nuclear antigen 53 kDa (MINA53) and nucleolar protein 66 kDa (NO66) catalyzes histidyl hydroxylation of human ribosomal proteins uL15 (L27A) and uL2 (L8), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The role of heme proteins and the potentially important roles of the mitochondria and the respiratory chain remain to be fully explored. Other areas likely to be of future interest include the regulation of translation in hypoxia (109) and the nearly unstudied modulation of the host by fungal pathogens in hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…89 PTex-enriched proteins contain a WD40 fold; a domain found to directly bind snRNA in Gemin 5 (41), taking part in rRNA biogenesis (Erb1 (42)) and found in RBPs (1). Other enriched domains are: AAA (AT-Pase, see below) fold, tetratrico peptide repeat region (TPR) as found in the yeast Clf1p splicing factor (43), Ski complex (44) and the translation terminator Nro1 (45), and the CH domain which is found among actin-binding proteins (3).…”
Section: A Global Snapshot Of Human Rna-protein Complexesmentioning
confidence: 99%